1996
DOI: 10.1111/j.1745-4573.1996.tb00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Acceptance of Lamb Versus Beef and Pork by Consumers and Experienced Sensory Panelists

Abstract: Lamb, beef, and pork patties containing ≈ 21% fat were pan‐fried to 71C and evaluated by consumers (n=71) and experienced laboratory sensory panelists (n=12) to determine to what extent panelists could correctly identify the species and to document the probable basis of their identification. When six samples (the first three samples representing the first servings of the three species and the next three representing the second servings) were served one at a time, 59%, 49%, and 32% of consumer panelists correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Experiments have been conducted in many countries to evaluate sheep breeds for growth and carcass traits (e.g., Carter and Kirton, 1975;Croston et al, 1987;Freking and Leymaster, 2004). Comprehensive characterization of breeds also should include sensory traits to provide relevant information for highly competitive markets, as attributes of lamb meat affect whether consumers choose lamb instead of beef, pork, poultry, or fi sh, or perhaps discourage consumption of lamb (Rhee and Yiprin, 1996). Although interest in attributes that affect palatability of lamb is increasing (Johnson et al, 2005), limited research has been directed toward evaluating breed effects on sensory traits of sheep (Clarke et al, 1996;Duckett and Effects of breed of sire on carcass composition and sensory traits of lamb 1…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have been conducted in many countries to evaluate sheep breeds for growth and carcass traits (e.g., Carter and Kirton, 1975;Croston et al, 1987;Freking and Leymaster, 2004). Comprehensive characterization of breeds also should include sensory traits to provide relevant information for highly competitive markets, as attributes of lamb meat affect whether consumers choose lamb instead of beef, pork, poultry, or fi sh, or perhaps discourage consumption of lamb (Rhee and Yiprin, 1996). Although interest in attributes that affect palatability of lamb is increasing (Johnson et al, 2005), limited research has been directed toward evaluating breed effects on sensory traits of sheep (Clarke et al, 1996;Duckett and Effects of breed of sire on carcass composition and sensory traits of lamb 1…”
Section: Introductionmentioning
confidence: 99%
“…Typical sheep odour and flavour is often associated with an unpleasant smell and therefore lower consumer acceptance of sheep products such as lamb (Prescott et al, 2001;Rhee and Ziprin, 1996;Wong et al, 1975). For lamb production, choosing a certain terminal-sire breed would be a rather simple and practicable opportunity to achieve better consumer acceptance if this reduced species-specific odour and flavour.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have indicated that consumer acceptance of sheep meat was influenced by its species-related flavor (Batcher et al, 1969;Smith and Young, 1991;Rhee and Ziprin, 1996). The sheep meat flavor can be more intense for fine-wool breeds than for coarsewool breeds (Cramer et al, 1970) and more intense for mutton compared to lamb (Batcher et al, 1969;Sink and Caporaso, 1977).…”
Section: Introductionmentioning
confidence: 99%